O regime diferenciado de contratações na INFRAERO - Aragão, Ferdinando Araújo de Mesquita (2015)
The objective of this article is to analise the effectiveness of the Differentiated Regime Signings in light of Law 8666/93 (LGL) taking into consideration the rational use of budget resources, bidding time and employed staff. An extensive persue of colleting data from INFRAERO, enabled the elaboration of a theoretical reference as well as the pratical application of promoted innovations and of the objetive´s results. Thereafter, it is possible to consider other aspects with contribute to the efficiency of public procurement which escape from legal definitions as it includes economics aspects, that should be observed in order to obtain clear definitions, coherent with the realities and necessities not only of the public realm, but of the private´s as well.